Coupled influence of precipitation regimes and seedling emergence time on the reproductive strategy in Chloris virgata - Wang, Ying; Chen, Jiawei; Huang, Yige; Mu, Zhongsheng; Wang, Changfu (PeerJ, 2020)
Precipitation regime and seedling emergence time both influence plant growth and reproduction. However, little attention has been given to the effects of these combined factors on the reproductive strategy of Chloris virgata, which is a vital species in Songnen grassland. Here, we simulated the changes in the precipitation regime and seedling emergence time to evaluate tiller traits and seed production. The results showed that tiller number behaved similarly among three precipitation regimes when sowed on 15 May (T1), while it increased significantly with precipitation regimes when sowed on 15 June (T2) and 15 July (T3). Tiller number decreased significantly with the seedling emergence time under the same water supply treatment. The proportional allocation of reproductive tiller number to total tiller number was significantly higher at T3 than at T1 and T2. Seed number remained similar under different precipitation regimes at T2 and T3, whereas it was significantly lower under low precipitation than under other water levels at T1. Seed number reached the maximum values at T2 under the same level of precipitation treatment. Seed size was significantly lower under low precipitation compared to other water supply treatments and the lowest values in seed size, about 0.5 mg, occurred at T2 under all the precipitation regimes. The lowest values in spike number were under low precipitation at all seedling emergence times. Seed yield exhibited similar trends with seed size under different precipitation regimes, while the greatest gains in these values were at T1 under all the precipitation regimes. Our findings showed that simulated precipitation regimes and seedling emergence time affected the reproductive strategy of C. virgata. Typical and high precipitation, as well as early seedling emergence, will improve the seed yield and seed quality in this species.
Keywords: Reproduction; Seed size; Seed yield; Tiller trait